Reinforcement in concrete piles embedded in sand - Salman, F.A.; Mohammed, M.M.; Shirazi, S.M.; Jameel, Mohammed (Academic Journals, 2010)
In this study, the necessity of reinforcement in concrete pile (bored or driven) is assessed. The soil was assumed to be unsaturated and homogeneous sandy soil. Throughout the study, a finite element computer program was used and the pile was modeled as a beam-on-elastic foundation. The soil is represented by discrete spring. The stiffness of each spring is considered to be linearly variable with depth. The moment loading, lateral loading, pile length, pile diameter, in addition to the angle of internal friction and soil density were taken as parameter to study their effect on the extent of reinforcement along the pile shaft. It is concluded that for piles embedded in sand, a length of reinforcement not less than 40 of pile length for bored piles and 20 for driven piles is needed.